Prosthetically adverse implant position: an aesthetic surgical-prosthetic solution. Case report - Andrés Chale-Yaringaño; Yuri Castro-Rodríguez; Sixto Grados-Pomarino (Universidad de Concepción., 2018)
Clinical case of a 43-year-old female patient treated at the clinic of Universidad Nacional Mayor de San Marcos, Peru, in 2015 for aesthetic problems in the activation of a unitary implant placed at a distal and vestibular direction from the ideal position. The clinical examination revealed the vestibularization of the implant at the level of the upper right central incisor with the healing abutment visible above the gingival line and high gingival smile. Connective tissue grafts and ovoid pontics were carried out in order to improve the characteristics of the peri-implant tissue. This clinical case evidenced an improvement of the soft tissue profile and patient satisfaction regarding her smile. The management of a vestibularized implant may be solved through the management of ovoid pontics and connective tissue grafts